Correlation between the deformation microstructure after rolling and the recrystallization nucleation of a non-oriented electrical steel. Issue 1 (July 2015) - Hsu, W C; Sun, P L; Kao, P W; Chang, L
Abstract: The characteristics of the cold-rolled (CR) microstructure of a non-oriented electrical steel after 50-90% cold rolling were studied using electron backscatter diffraction. The local heterogeneity of the deformed microstructure was found to consist of high misorientation regions (HMRs) and low misorientation regions (LMRs) according to local misorientation and size. The overall orientation distribution of HMRs was obtained accordingly and was compared to that of the fully recrystallized sample. Moreover, the CR and partially recrystallized states of the same area were analyzed and compared. The position and orientation of each HMR can be identified individually, and be correlated with the recrystallization nuclei. The HMRs were distributed near the original high angle boundaries at 50% rolling reduction, but extended into the grain interiors with increasing rolling reductions to 70% and 90%. As a result, the recrystallized nuclei for the 50% cold rolled sample were mainly distributed at the original high angle boundaries and the triple junctions, whereas extended nucleation at the deformation bands was observed for the high rolling reduction samples. Good correlation of the orientation between the HMRs and the recrystallized nuclei were observed.